Sentido Que Le Dan Las Integrantes Del Equipo De Futbol De Salón Femenino De La Universidad Del Quindío, A Las Relaciones De Pareja Dentro De Su Proceso Deportivo (2014)
Objective: To reveal the meaning they give the athletes the influence of relationships in women's sports processes. Methodology: This research work is based descriptive cut from hermeneutics to establish the procedure for expressing an opinion from the acting ability from the personal history and leaning on a kind of ethnographic research, allowing to know the point of view of each person taking into account their culture and education, as according to the company and its training will be completely different opinions managing to make a more general and open to learning about their opinions as to the difference in study thoughts. Findings: improvement was noted that speaking of relationships within a sports group varies depending on the culture and personnel thought everyone because for some it will be normal and positive while others will be a future problem. Conclusions: different views or theories that address the issue of relationships provide a more valuable insight which broadens the horizon of current ideas and to make better decisions regarding rules and procedures to carry out in the different teams work.